Filling gaps: pentatomids (Hemiptera: Heteroptera) from Boraceia Biological Station (São Paulo, Brazil) with a preliminary checklist for the Atlantic Rain Forest - Talita Roell; Guilherme Enrique Luisi López; Cristiano Feldens Schwertner (Papéis Avulsos de Zoologia)
Abstract The Boraceia Biological Station (BBS) is located in the Salesópolis municipality, State of São Paulo, and represents an important natural protected area of the Atlantic Rain Forest in one of Brazil’s most urbanized states. In this work, an inventory for the BBS was compiled, using specimens deposited in the Zoology Museum of the University of São Paulo and through consultation of bibliography. We list 36 species of stink bugs (Hemiptera: Pentatomidae) collected over 80 years. Six species were recorded for the first time in the State of São Paulo. The inventory represents the first one comparing the diversity of species from BBS with the recorded diversity of the Atlantic Rain Forest. We also present a preliminary checklist of pentatomids of the Atlantic Rain Forest and highlight the importance of preserving natural areas in the Atlantic Rain Forest.